Synergies of flavor anomalies with top-quark physics in the Standard Model Effective Field Theory and direct searches - Bißmann, Stefan (Technische Universität Dortmund, 2021)
This thesis comprises a study on opportunities for physics beyond the Standard Model (BSM) guided by the flavor anomalies. Aiming at linking the top-quark sector of the Standard Model Effective Field Theory (SMEFT) to the anomalies in b → s transitions, we perform a global fit to top-quark data detailing on the validity of the SMEFT framework, and highlight benefits and challenges of combining multiple measurements in a combined fit. To combine top-quark and beauty data we perform a first joined fit of three SMEFT Wilson coefficients to tt̄γ and b → sγ data. We work out the steps needed for linking top-quark and B physics within SMEFT, and demonstrate how the complementarity of both sectors enhances constraints significantly. Extending our setup, we analyze semileptonic four-fermion operators, which are of high interest in the context of anomalies seen in b → sμ+μ− data, in a combined fit to top-quark, Zbb, and B-physics observables using present data as well as future scenarios of HL-LHC, Belle II, and a future lepton collider. We observe powerful synergies between top-quark and beauty physics, which open new directions for model-independent searches. To complement our analysis, we investigate the possibility that BSM physics can be well within the reach of the LHC while still accommodating the anomalies within the lepton anomalous magnetic moments and lifting several shortcomings of the Standard Model (SM). The models are an asymptotically safe extension of the SM featuring potentially light vector-like leptons and additional scalars with a non-trivial flavor structure. We perform a detailed study of implications for discovery at the LHC exploiting unique flavor signatures to construct null- tests of the SM, and find that Run 2 data can be sufficient to detect BSM physics, indicating that new physics might be just around the corner.

Diese Dissertation beinhaltet eine Studie zur Entdeckung von Physik jenseits des Standard Modells (BSM) geleitet durch die Flavor-Anomalien. Mit dem Ziel, den Top-Quark Bereich der Standard Model Effective Field Theory (SMEFT) mit den Anomalien in b → s Übergän- gen zu verbinden, führen wir zunächst einen globalen Fit an Top-Quark Messungen durch, in dem wir die Gültigkeit des SMEFT-Ansatzes sowie Vorteile und Herausforderungen, die in der Kombination verschiedener Datensätze entstehen, diskutieren. Anschließend führen wir eine erste kombinierte Analyse von Top-Quark und Beauty Daten durch und fitten drei SMEFT Wilson Koeffizienten an tt̄γ and b → sγ Daten. Wir beschreiben die notwendigen Schritte für die Analyse und zeigen, wie Unterschiede in der Sensitivität die Resultate deutlich verbessern. Wir erweitern diese Studie und betrachten semileptonische Operatoren, die im starken Zusammenhang zu den Anomalien in b → sμ+μ− Messungen stehen, in einem Fit an Top-Quark, Zbb, und B-Physik Observablen im Kontext aktueller Messungen sowie mehrerer Zukunftsszenarien für HL-LHC, Belle II, und einem Lepton Collider. Unsere Analyse zeigt eine starke Verbindung von Top-Quark und Beauty Observablen auf, die neue Möglichkeiten für modellunabhängige Fits ermöglichen. Um unsere Analyse abzurunden, untersuchen wir den Fall, dass BSM Physik am LHC produziert werden könnte. Diese neue Physik kann sowohl die Anomalien in den magnetischen Momenten der Leptonen erklären als auch mehrere Prob- leme des Standard Modells beheben. Wir betrachten dazu zwei asymptotisch sichere Modelle mit vektorartigen Leptonen und Skalaren mit einer nicht-trivialen Falvorstruktur und führen eine detaillierte Analyse für eine Entdeckung am LHC durch. Wir konstruieren Nulltests und stellen fest, dass der Run 2 Datensatz ausreichen könnte, um BSM Physik zu entdecken.
Keywords: Search for new physics; Beyond the Standard Model; SMEFT; Effective field theory; Flavor anomalies; Top-quark physics; Flavor physics; Global fits; 530; Standardmodell <Elementarteilchenphysik>; Erweiterung; t-Quark